PERLINDUNGAN HUKUM TERHADAP RENDAHNYA KESEJAHTERAAN SOSIAL DI KALIMANTAN TIMUR (TINJAUAN YURIDIS PERATURAN PRESIDEN NOMOR 3 TAHUN 2016) - Virvina Lire (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe condition of the Indonesian people at this time is still felt very apprehensive. The number of people who do not have decent welfare for their survival become one of the main discussion in this thesis. The lack of employment, uneven development and population density in each region is one of the reasons why many unemployed in Indonesia. The Presidential Regulation of the Republic of Indonesia number 3 of 2016 on the acceleration of the implementation of the National strategic project fulfills the elements of (a) regulations on human behavior in the community; (B) The Rules are held by authorized bodies; (C) The rule is coercive; (D) Sanctions against such breaches of the rule are strict. Presidential Regulation No. 3 of 2016 on the Acceleration of the Implementation of National Strategic Projects meets the point of view of an economist's material legal source. It aims to meet the basic needs and improve the welfare of the community. And can be clarified as a law in the material sense that fundamental every decision of the Government in this case dalah President who according to its contents directly bind each resident. Legal Protection against the problem of low social welfare in East Kalimantan: 1) Menurtu UUD 1945 Article 27; The provisions of article 27 paragraph (2) of the 1945 Constitution, every citizen of the work and livelihood that is suitable for humanity. 2) according to the Social Welfare Law the main subject set forth in this Law is, among others, the fulfillment of the right to basic needs, the provision of comprehensive and professional social welfare, and the protection of the community.